Characteristics of Anemia in Children Aged 6 Months to 5 Years Attending External Consultations at a Pediatric Hospital in Lisbon, Portugal - Réka Maulide Cane; Sérgio Chicumbe; Youssouf Keita; Anaxore Casimiro; Bárbara Martins Saraiva; Joana Vasconcelos; Beatriz Luzio Vaz; Afonso Sousa; Mafalda Cabral; Francisco Branco Caetano; Luís Varandas; Isabel Craveiro (Children)
Background/Objectives: Childhood anemia remains a serious public health issue, negatively affecting cognitive and psychomotor development, with repercussions on school performance and adult productivity. This study aimed to characterize the profile of children aged 6 months to 5 years diagnosed with or at risk of anemia who attended a pediatric hospital in Lisbon, Portugal. Methods: A hospital-based, cross-sectional descriptive study was conducted from September 2023 to September 2024. Descriptive statistics, including frequency distributions and cross-tabulations, summarized participant characteristics and key variables. Results: We observed that 33.3% (74/222) of the children were either anemic or at risk of anemia. Among these, 93.2% (69/74) were confirmed anemic or at risk based on hemoglobin levels. Five children (6.8%) had normal hemoglobin but abnormal red-cell indices, with microcytic (60.0%; 3/5) or normocytic (40.0%; 2/5) patterns. Anemia rates were higher in males (55.1%), children aged 24–59 months, those residing in the Metropolitan Lisbon Area (82.6%), children whose caregivers had only basic or secondary education (58.0%), and those whose mothers were born in foreign countries (48.4%). Microcytic red-cell indices were observed in 63.1% of cases. Serum iron results indicated that 32.0% were pre-anemic and 40.0% anemic. Ferritin levels showed iron-deficiency anemia in 22.2% of tested cases. In addition, 33.3% carried the sickle cell trait, and 35.0% had elevated C-reactive protein, suggesting anemia of inflammation. Conclusions: Anemia is a moderate public health issue, mainly affecting children with less-educated caregivers and migrant mothers. Targeted public health actions, including systematic screening, caregiver education, and multiculturally sensitive interventions, are crucial to address anemia.